Beer Turbidity Part 1: A Review of Factors and Solutions. (1st April 2021) - Kahle, Eva-Maria; Zarnkow, Martin; Jacob, Fritz
Abstract: Turbidity in beer will continue to be a major topic as many origins of haze have already been discovered, but it is not always possible to identify its immediate cause. In addition to beer foam, one of the most important visual quality characteristics of filtered beers is gloss fineness. Consequently, in the case of an undesirable haze, it is first necessary to identify the haze particles and how to remove them. The topic is covered in two sections. This review labelled Part 1 and a second review labelled Part 2. Part 1 addresses turbidity in general, the causes and origins of turbidity and the different analytical methods for turbidity identification and removal. Part 2 focuses on Raman spectroscopy and provides a general overview of the physical basics, the areas of application, possible gaps and the challenge for its use for identifying turbidity in beer and beverages.